Web Vulnerability Assessment and Maturity Model Analysis on Indonesia Higher Education - IGN, Mantra; Muhammad Syarif, Hartawan; Hoga, Saragih; Aedah, Abd Rahman (2019)
College websites are websites that are used as media and means of campus information. Since the website is widely accessible, the level of security on the website must always be maintained. To see the level of web security, it can be done by testing the security vulnerability of the web. The test results using the tools Nessus and Skipfish, on the websites of several universities in Jakarta, show that there are still several vulnerabilities. This vulnerability will affect the maturity level of the web site security. The results of vulnerability testing show that as many as 60% of the total 33 web sites have a maturity level below number 3. This indicates that the level of vulnerability on the web site is still high.